Thermodynamics of Various Entropies in Specific Modified Gravity with Particle Creation - Abdul Jawad; Shamaila Rani; Salman Rafique (Advances in High Energy Physics)
We consider the particle creation scenario in the dynamical Chern-Simons modified gravity in the presence of perfect fluid equation of state p=(γ-1)ρ. By assuming various modified entropies (Bekenstein entropy logarithmic entropy, power law correction, and Renyi entropy), we investigate the first law of thermodynamics and generalized second law of thermodynamics on the apparent horizon. In the presence of particle creation rate, we discuss the generalized second law of thermodynamics and thermal equilibrium condition. It is found that thermodynamics laws and equilibrium condition remain valid under certain conditions of parameters.